A study of incidental appendectomy during diagnostic laparoscopy performed to evaluate the causes of lower abdominal pain - Shah, Vishal S.; Parmar, Alpesh J.; Ninama, Shireesh M.; Patel, Harsh A. (International Surgery Journal, 2022)
Background: Diagnostic laparoscopy is a minimally invasive method for the diagnosis of intra-abdominal diseases by direct inspection of intra-abdominal organs whenever there is a diagnostic dilemma even after routine diagnostic workup. Incidental appendectomy is defined as the removal of a clinically normal appendix during non-appendiceal surgery. The study is performed to evaluate the causes of lower abdominal pain during diagnostic laparoscopy and to determine the benefits of incidental appendectomy. Methods: This study, performed at the department of surgery, B. J. medical college, Ahmedabad from May 2012 to October 2014 is a prospective study. Incidental appendectomy was performed during diagnostic laparoscopy in 30 patients with abdominal pain. Criteria such as symptomatology, aetiology of pain as found on laparoscopy, post-operative pain relief and complications were analysed. Results: Nearly two third of the patients who presented with intractable lower abdominal pain were females. Mesenteric lymphadenopathy was the commonest per-operative finding affecting half of the patients, followed by adhesions present in about one quarter of the patients. Gynaecological conditions represented about one third of the cases. All, except one patient, had satisfactory pain relief and no complications of incidental appendectomy over a one year follow up. Conclusions: We conclude that diagnostic laparoscopy is a very good and accurate tool to diagnose the causes of abdominal pain and should be routinely used where radiological investigations are inconclusive. Incidental appendectomy indeed has many advantages when performed in an appropriate age group and proper setting.